The Effect of Mind Mapping Teaching Technique to The Writing Ability of Tenth Grade Students of Sma S YP HKBP 1 Pematangsiantar in a Descriptive Text - Sanggam Siahaan; Irene Adryani Nababan; Carolina Carolina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to know the effect of mind mapping teaching technique to the writing ability of tenth grade students of SMA S YP HKBP 1 Pematangsiantar in a descriptive text. This research was quantitative research. To get the answer for the research, the researcher used quasi-experimental design. The population of this research was tenth grade students of SMA S YP HKBP 1 Pematangsiantar that consisted of four classes. The sampling technique in this research was purposive sampling. The sample consisted of two classes, namely class X-3 used the mind mapping teaching technique as the experimental class and class X-4 used the guided writing teaching technique as the control class. To collect the data, the researcher used the test. The researcher used essay test as the instrument of the research. Paired-samples t-test was used by the researcher to test the hypothesis. The result of the research showed that the effect of mind mapping teaching technique was more significant than guided writing teaching technique. It was proved by the t-test value (2.52) > t-table (1,67). It means that Ha was accepted and H0 was rejected. The writing ability of students in a descriptive text in experimental class was improved since they were taught by mind mapping teaching technique. It is recommended that the result of this research can be used in order to develop the teaching technique at school.